Symposium 5: Quality Towards an Expected Harmony: Pedagogy and Innovation Speaking Together About Technology - Lebrun, Marcel (Proceedings of the International Conference on Networked Learning, 2004)
In this paper, we will try to elaborate, in the field of educational technology in higher education, the following hypothesis: Students learn, teachers learn and furthermore institutions learn. The coherence of these various levels (students, teachers, institutions) around learning may be considered as a guide and as a sign of an expected educational quality. In this case, the general models for learning and for pedagogical setup development may be used to develop new teaching or training methods, to promote innovation in institutions and to assess quality. After a short presentation of our “ objectives – methods – tools ” reference model, we will use it to organize and to assess the question of the added value of ICT in learning. These factors of learning boosted by ICT define a learning model consistent with learning factors as proposed by education sciences. Then, the deduced learning model will be used to understand and to foster teacher training and innovation in institutions.